MATERIAL TRANSFER AGREEMENT SEBAGAI SARANA PERLINDUNGAN HUKUM PARA PIHAK DALAM PERJANJIAN PENGALIHAN MATERI BIOLOGI - Sogar Simamora; Agung Sudjatmiko; Ria Setyawati (Yuridika, 2016)
Biological material is largely a free component, but the development of these materials can be objects that have commercial high value. Thus, the biological material is also associated with the ownership and control should be regulated by the misuse of biological materials hukum. According to the characteristics of MTA as a civil agreement, the parties will be decisive in the formulation of the agreement, but the characteristics of biological materials, including viruses, which can endanger the safety and threaten public health requires the use of surveillance capabilities sampled by the competent authority. Thus, the protection of the right to material biologidan implementation monitoring system redirects biological materials need to be studied in detail for the purpose of sharing microbiological material for the benefit of mankind could reached . Indonesia's cases refusal to carry through the mechanism of virus sharing GISN (Global Influenza Surveillance Network) in the system of the World Health Organization (wHO) in 2007, the result of a lack of regulations concerning the transfer of biological material not truly perfect